Implementation of Changes in the Use of Agricultural Land to Non-Agriculture in the Land Office of Pemalang District (2011-2013) - Suryo Haj Hasmoro (Unnes Law Journal, 2019)
The purpose of this study was to (1) analyze the implementation of the licensing change of use of agricultural land to non-agricultural; (2) analyze the obstacles encountered by the Land Office and the citizens in the transition function of agricultural land into non-agricultural. This research is empirical juridical law with analytical descriptive research. Source of research data derived from primary and secondary data. The technique of collecting data using interviews (Land Office employees and citizens Pemalang) and documentation then analyzed descriptively qualitative. Results of this study are (1) The licensing change of use of agricultural land to non-agricultural can be done by private masyarat citizens or by the developer / investor, which process comprises: (a) the applicant making the request; (b) the payment of administrative costs, (c) review of the field consisting of the research process, data processing and manufacturing considerations technique, (d) the delivery of judgment technique to the Regent in the minutes of the Assembly Examination Committee for consideration, (e) decision of the application is accepted or denied, and (f) submission of the decision for a permit to the applicant. (2) The constraints encountered by the Land Office is the difference in the deliberations of the Technical Advisory Team Land when reviewing the location, and the public / applicant had been doing construction on agricultural land that has not been transformed to enable.